FUNÇÕES EXECUTIVAS E DEPENDÊNCIA DO TABACO EM ADULTOS DO MUNICÍPIO DE IRATI - Bortoli, Jussara de (2015)
Fighting smoking has been considered as one of the great challenges of the contemporary world, given that it is perceived as a disease that is directly related to nicotine dependence, psychoactive component of the cigarette, which is responsible for a large number of illnesses and deaths. In addition to these effects, there is still implications of smoking in the functioning of brain functions, since when ingested nicotine also acts on the brain and can cause changes in executive functions. These functions can be understood as a set of cognitive skills that are necessary to perform behaviors directed to certain goals, involving the adaptive capacity of the subject across the various demands from the environment. In this sense, a change in executive functions, could cause a loss in health and so the quality of life of the individual as belonging to a particular community. Therefore, an assessment of executive function can influence to a better understanding of smoking, thereby strengthening several areas that seek to understand it. Objectives: To analyze the possible changes of executive functions in adult smokers in the city of Irati. The evaluated executives components were: working memory, attention focused, sustained and divided. Method: A total of 76 subjects, 38 smokers and 38 nonsmokers aged between 30 and 50 years. The instruments were, respectively, Concentrated Attention Test (AC), the subscale of the WAIS-III Digit and the Color Trails Test (TTC). Results: In the test (TTC) smokers to 8th grade had a higher average compared to smokers above the 8th grade. However, revealed no statistically significant difference. Total score of tests (AC) and Digits, smokers and nonsmokers with schooling above the 8th grade had mean higher compared to smokers and nonsmokers with education up to 8th grade. However, there was no statistically significant difference between the groups in the AC test and Digits direct phase. For reverse phase digit of the instrument, it is possible to mention that there was a trend to consider it significant. Conclusion: Overall, there was no difference between smokers and nonsmokers as executive functions evaluated in tests, Concentrated Attention, Colored trails and Digit Direct phase. You Digits reverse phase, there was a tendency to be significant.